Inorganic nitrate supplementation improves muscle oxygenation, O₂ uptake kinetics, and exercise tolerance at high but not low pedal rates - Bailey, Stephen J; Varnham, Richard L; DiMenna, Fred J; Breese, Brynmor C; Wylie, Lee J; Jones, Andrew M (Journal of applied physiology (1985), 2015)
We tested the hypothesis that inorganic nitrate (NO3 (-)) supplementation would improve muscle oxygenation, pulmonary oxygen uptake (V̇o2) kinetics, and exercise tolerance (Tlim) to a greater extent when cycling at high compared with low pedal rates. In a randomized, placebo-controlled cross-over study, seven subjects (mean ± SD, age 21 ± 2 yr, body mass 86 ± 10 kg) completed severe-intensity step cycle tests at pedal cadences of 35 rpm and 115 rpm during separate nine-day supplementation periods with NO3 (-)-rich beetroot juice (BR) (providing 8.4 mmol NO3 (-)/day) and placebo (PLA). Compared with PLA, plasma nitrite concentration increased 178% with BR (P < 0.01). There were no significant differences in muscle oxyhemoglobin concentration ([O2Hb]), phase II V̇o2 kinetics, or Tlim between BR and PLA when cycling at 35 rpm (P > 0.05). However, when cycling at 115 rpm, muscle [O2Hb] was higher at baseline and throughout exercise, phase II V̇o2 kinetics was faster (47 ± 16 s vs. 61 ± 25 s; P < 0.05), and Tlim was greater (362 ± 137 s vs. 297 ± 79 s; P < 0.05) with BR compared with PLA. These results suggest that short-term BR supplementation can increase muscle oxygenation, expedite the adjustment of oxidative metabolism, and enhance exercise tolerance when cycling at a high, but not a low, pedal cadence in healthy recreationally active subjects. These findings support recent observations that NO3 (-) supplementation may be particularly effective at improving physiological and functional responses in type II muscle fibers.